Memahami Etos Kerja Sebagai Wujud Amal Saleh - Bina Prima Panggayuh; Siti Khotijah Ayu; Nayla Putri Muzdalifah; Syasya Anasaskia; Fiantika Iswandari Az-Zahra (Yayasan Al-Afif, 2025)
This study examines Islamic work ethic as a form of amal saleh, reflecting obedience, responsibility, and professionalism of Muslims. Using library research and qualitative analysis, the study reviews books, journals, and scholarly articles. Findings indicate that Islamic work ethic emphasizes honesty, discipline, trustworthiness (amanah), professionalism (itqan), sincerity (ikhlas), independence, and diligence. Its application in education, family, and workplace settings enhances productivity, integrity, social responsibility, and shapes quality character beneficial to society. The study provides guidance for educators, parents, and professionals to cultivate an effective Islamic work ethic that is both productive and considered an act of worship.